Environmental Health and Preventive Medicine - Inadera, Hidekuni
The official journal of the Japanese Society for Hygiene, Environmental Health and Preventive Medicine (EHPM) brings a comprehensive approach to prevention and environmental health related to medical, biological, molecular biological, genetic, physical, psychosocial, chemical, and other environmental factors. EHPM features definitive studies on human health sciences and provides comprehensive and unique information to a worldwide readership.  International authors publishing in EHPM can request coverage of the journal’s article-processing charge (APC) by the Japanese Society for Hygiene, so they will not have to pay the APC themselves if the article is accepted. This must be requested during the article submission process by entering a code that can be obtained from the Society office (jsh@nacos.com).